Diffusely Abnormal White Matter, T2 Burden of Disease, and Brain Volume in Relapsing‐Remitting Multiple Sclerosis. Issue 1 (30th October 2018) - Vertinsky, Alexandra T.; Li, David K.B.; Vavasour, Irene M.; Miropolsky, Vladislav; Zhao, Guojun; Zhao, Yinshan; Riddehough, Andrew; Moore, G.R. Wayne; Traboulsee, Anthony; Laule, Cornelia
ABSTRACT: BACKGROUND AND PURPOSE: Multiple sclerosis (MS) diffusely abnormal white matter (DAWM) is a mildly hyperintense magnetic resonance imaging abnormality distinct from typical lesions. Our goal was to investigate the prevalence and natural history of DAWM in a large cohort ( n = 348) of relapsing–remitting MS (RRMS) patients. METHODS: The presence of DAWM and relationship to changes in T2 burden of disease (BOD), brain volume (brain fractional ratio, BFR), and disability (Expanded Disability Status Scale, EDSS) were investigated at baseline and year 7–8 (long‐term follow‐up, LTF). RESULTS: DAWM was present in 25.3% (88 of 348) of patients at baseline. At LTF, DAWM was unchanged in 69.3% (61 of 88), decreased in 28.4% (25 of 88), and increased in 2.3% (2 of 88) of patients. Baseline BOD and change in BOD did not significantly differ between patients with and without DAWM. DAWM was associated with greater reduction in BFR at LTF ( P = .038). DAWM and DAWM change did not predict EDSS or EDSS progression. CONCLUSIONS: DAWM is present in a quarter of RRMS patients, and rarely increases or develops de novo. DAWM predicts brain atrophy but does not predict physical disability. Because of its posterior periventricular location, further investigation is warranted to evaluate its relationship to other measures of disability, including visual spatial processing and cognitive function.